POMPOLIKS IMPETIGENISATA PADA BAYI PEREMPUAN GIZI KURANG USIA 16 BULAN: SEBUAH LAPORAN KASUS - Kadek Rosa Puspita (Jurnal Medika Hutama, 2022)
Abstract Introduction: Pompholyx is a skin disorder characterized by vesicles/bullae on the lateral sides of the fingers of palms/soles, palms, and soles. Case: A 16-month-old baby girl with poor nutrition was complained of having blisters on her palms and soles including fingers. Feels itchy, followed by the formation of bullae which then undergo eruption and desquamation. Oral triamcinolone acetonide and cetirizine therapy are given, as well as a topical combination of gentamicin and salicylic acid. Discussion: Although most cases occur at the age of 10-40 years, it does not rule out any possibility of occurring at the age of under 10 years. Endogenous and exogenous factors play roles in this disorder. Anti-inflammatory oral therapy as well as antihistamine can help reduce symptoms and severity. Similarly, the topical administration of antibiotics. Conclusion: Pompholyx can occur at the age of under 10 years. The goal of therapy is to overcome the formation of blisters and inflammation, relieve itching complaints, and prevent/treat infections.